(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The purpose of the study was to find out effects of different types emotions on shopper’s decisions. The subjects were 120 costumers, who had purchased different items from Archies shops located in Dainik Bhasker Mall, Race Course Road, Gwalior, M. P. it is evident from the result that male customers are greater in number in comparison to females customers. However there are no effects being found of occupation customers visiting to the retail shop in the mall. Further it has being found that greater percentage of customers buy product only when there positive emotions of happiness and surprise gets evoked, in comparison to customers with negative emotions of sadness or disgust or anger or fear.